Impacts of water vapor on Saharan air layer radiative heating - Gutleben, Manuel; Groß, Silke; Wirth, Martin; Emde, Claudia; Mayer, Bernhard (Geophysical Research Letters, 2019)
Abstract Airborne lidar observations of long-range transported Saharan air layers in the western North Atlantic trades indicate increased amounts of water vapor within the dust layers compared to the surrounding dry free atmosphere. This study investigates the impact of such enhanced water vapor concentrations on radiative heating. Therefore, spatially high resolved airborne high spectral resolution and differential absorption lidar measurements are used for the parametrization of aerosol optical properties and water vapor concentrations in radiative transfer calculations. Heating rates that are calculated under consideration of the measured water vapor distribution strongly differ from heating rates that are derived under assumption of an atmospheric reference water vapor profile which is steadily decreasing with altitude. Results highlight that water vapor represents a major radiative driver for dust layer vertical mixing and the maintenance of bounding inversions at the top and bottom of the dust layer.